Water Disconnections and NWSC Performance in Iganga Municipality, Uganda - Asinai, Lilian; Barigayomwe, Rogers (East African Nature and Science Organization, 2024)
This study investigates the relationship between water disconnections and bills receivable management at the National Water and Sewerage Corporation (NWSC) in Iganga Municipality. The research uses a mixed-methods approach to analyse customer perceptions regarding disconnections and their impact on revenue recovery. The findings indicate a positive correlation between the disconnection of water services due to non-payment and the financial performance of the NWSC, with the corporation recovering over 100 billion UGX annually from disconnections and reconnection fees. Despite a total billing of 3,049,102,366 UGX for the last financial year, the NWSC managed to collect only 2,728,709,173 UGX, resulting in a collection efficiency of 91%. However, infrastructure issues, economic uncertainties, and customer financial hardships affect overall revenue collection efficiency. Based on these findings, the study recommends enhanced customer engagement, improved infrastructure, flexible payment options, and the use of technology to optimize billing and revenue collection processes